PENGARUH PENDIDIKAN DAN PELATIHAN SERTA KOMPETENSI MANAJERIAL TERHADAP KINERJA KEPALA SEKOLAH - Wiwu Ulandari; edhy rustan (Universitas Mercu Buana, 2021)
The headmaster's performance is influenced by several factors. The purpose of this study was to examine the effect of education and training and managerial competence on the performance of school principals. The method used in this research is quantitative with an ex-post facto design. Sampling was selected in a multistage manner from 19 State Senior High Schools in North Luwu Regency. Data were collected through observation and questionnaires for further data analysis with multiple regression. The test results show the effect of education and training on the performance of principals with a coefficient of 43.7%, the effect of managerial competence on the performance of principals with a coefficient of 52.5% and the effect of education and training and managerial competence on the performance of principals with a coefficient of 52, 6%. Thus, it is concluded that the implementation of education and training, as well as managerial competence, affect the performance of school principals.